Elevated Serum Homocysteine Concentrations in Severe Preeclampsia and Eclampsia - Begum, Shahnaj; Parveen, Nahid; Nahid, Sanzida (Ibrahim Cardiac Medical Journal, 2023)
Background & objective: Preeclampsia, a pregnancy-specific syndrome, is a major cause of maternal and perinatalmorbidity and mortality all over the world. Several studies have indicated that homocysteine concentrations areincreased in women with preeclampsia. However, there is still conflicting evidence on the extent to which elevatedmaternal homocysteine contributes to this deadly complication of pregnancy. The present study was, therefore,intended to see the association between serum homocysteine and preeclampsia. Methods: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology, Dhaka MedicalCollege Hospital, Dhaka over a period of 2 (two) years from July 2007 to June 2009. Pregnant women with gestationalage ranging between 24 – 40 weeks having preeclampsia or eclampsia were considered as cases, while gestationalage-matched pregnant women without preeclampsia and eclampsia were considered as controls. However, pregnancywith diabetes mellitus, known renal or hepatic disease, urinary tract infection, cardiovascular disease, and takinganti-epileptics were excluded from the study. A total of 100 pregnant women – 50 cases and 50 controls were selectedfor the study. Among the cases, 16 had mild preeclampsia, 17 had severe preeclampsia, and 17 had eclampsia. Result: Two-thirds of the cases and 60% of the controls were in their 3rd decade of life with no significant differencebetween the study groups (p = 0.651). There was no significant difference between the groups in terms of gravidityand gestational age. However, the past history of PE demonstrated its more significant presence in the case group thanthat in the control group (p = 0.030). Out of 50 cases, 30(60%) had severe proteinura (+++), 15(30%) had moderateproteinuria (++) and 5(10%) had mild proteinuria. The mean serum homocysteine level was significantly higher inmild PE (7.2±1.2 μmol/L) than that in normal pregnant women (5.3±1.0 μmol/L). The concentration of homocysteineincreases with the increase in severity of preeclampsia (p = 0.004) and turning preeclampsia into eclampsia (p =0.027). The data show as the grade of proteinuria increases progressively (from mild to severe) the concentrations ofhomocysteine level also increase progressively from 6.3 ± 1.6 μmol/L in mild proteinuria to 11.4 ± 3.7 μmol/L insevere proteinuria. Conclusion: The serum homocysteine level is significantly elevated in mild PE than that in normal pregnant women.The concentration of homocysteine increases further with the increase in the severity of preeclampsia and ineclampsia. Ibrahim Card Med J 2022; 12 (2): 10-14